The Practical Importance of Immunohistochemical Examination in Prostate Cancer - Abdukadirovich, Rakmanov Xamza (Journal of Science in Medicine and Life, 2024)
Transrectal ultrasound (TRUS) has traditionally been considered the primary imaging test of the prostate and is clinically important in both benign and malignant lesions, including benign prostatic hyperplasia (BPH), prostatitis, obstructive infertility, and prostate cancer (PCa). information. Currently, the main reasons patients are referred for TRUS are ultrasound for prostate cancer detection and evaluation and prostate biopsy. The accuracy of these studies depends in part on the cost of fixed ultrasound scanners. Transrectal ultrasound (TRUS) has traditionally been considered the primary imaging test of the prostate, providing clinically important information in both benign and malignant lesions, including benign prostatic hyperplasia (BPH), prostatitis, obstructive infertility, and prostate cancer (PCa). . Currently, the main reasons patients are referred for TRUS are ultrasound for prostate cancer detection and evaluation and prostate biopsy.